PERBEDAAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DAN MOTIVASI BELAJAR DENGAN PEMBELAJARAN BERBASIS MASALAH - Irham Habibi Harahap (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2017)
The aim of this research is to find out (1) the differences of mathematics problem solving ability of student who get the problem-based learning better than student who get direct learning, (2) the difference of students’ learning motivation who get problem-based learning better than student who get direct learning, (3) the level of students’ activity during the process of the problem-based learning takes place, (4) the process of students’ answers that taught with problem-based learning is better than direct learning. Thisresearch is a semi experimental research. The population of this study is the students of eighth grade of Junior High School that accredited A in Sibuhuan. Randomly, one school was chosen as a subject of this research, namely SMP Negeri 1 Barumun. Then randomly, selected two classes from seven classes The first experiment class was given a problem-based learning treatment and the second experiment class was given a direct learning treatment. Instrument which is used consisted of a test of mathematics problem solving ability, questionnaire of students’ learning motivation and observation sheets. Data analysis was done by covariance analysis (ANACOVA) and Mann-Whitney test. The result of this research is the whole students who get problem-based learning is significantly better than the mathematics problem solving ability and students’ learning motivation are compared with students who get direct learning, students’ activity in problem-based learning is effective and the process of students’ answer which get problem-based learning better than students who get direct learning.